2004
DOI: 10.1259/bjr/28611372
|View full text |Cite
|
Sign up to set email alerts
|

Partial thrombosis of an idiopathic azygos vein aneurysm

Abstract: Aneurysms of the azygos vein are often asymptomatic, detected on a chest radiograph simulating paratracheal mass. When the aneurysm is totally thrombosed, it is impossible to distinguish it from another cause of mediastinal mass. A case is presented in which partial thrombosis of the aneurysm and communication with the superior vena cava led to a diagnosis on angiography and CT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 5 publications
1
17
0
2
Order By: Relevance
“…Without the enhanced imaging, the tumour resembled bronchogenic cysts or foregut duplication cysts. Previous reports have shown that preoperative diagnoses include bronchogenic cysts, neurogenic tumours, and swollen lymph nodes 2, 3, 4.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Without the enhanced imaging, the tumour resembled bronchogenic cysts or foregut duplication cysts. Previous reports have shown that preoperative diagnoses include bronchogenic cysts, neurogenic tumours, and swollen lymph nodes 2, 3, 4.…”
Section: Discussionmentioning
confidence: 99%
“…However, as long as cases with ruptures and/or thrombosis 1, 4, 5 are reported, the surgical removal of the tumour should be considered the best approach for this type of tumour. Successful video‐assisted thoracic surgeries for this tumour have been reported.…”
Section: Discussionmentioning
confidence: 99%
“…1 It usually occurs in patients with vascular disease: portal hypertension, heart failure, malformation of the inferior vena cava including partial or total agenesia, or obstruction of the inferior vena cava by a tumor or other cause. 2 In this case, the origin of this aneurysm is unknown, although a congenital origin is suggested.…”
Section: Discussionmentioning
confidence: 99%
“…Idiopathic aneurysms of the azygos vein system (azygos vein, hemiazygos vein, and accessory hemiazygos vein) are rare, and there is no standard treatment (1)(2)(3)(4)(5). We herein report a case of an asymptomatic aneurysm of the accessory hemiazygos vein that was diagnosed based on the findings of contrast-enhanced computed tomography (CT) and angiography.…”
Section: Introductionmentioning
confidence: 97%